2019
DOI: 10.31289/agrisains.v1i2.247
|View full text |Cite
|
Sign up to set email alerts
|

Strategi Peningkatan Pendapatan Usahatani Padi Sawah di Kota Tebing Tinggi

Abstract: This study aims to determine the amount of income from lowland rice farming, determine the factors that affect the income of lowland rice farming and determine strategies for increasing the income of lowland rice farming in Tebing Tinggi City. The study was conducted in Tebing Tinggi City, North Sumatra Province which was carried out for 3 months, namely April - June 2017. The research approach was conducted descriptively through case studies. Data collection techniques carried out by observation, interviews, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“…The results showed that the use of labor is greater than other production costs, this means that labor is very influential on rice paddy farming, as research conducted by Ref. [14]. shows that labor is the largest component of the production costs of rice farming.…”
Section: Strategizingmentioning
confidence: 96%
“…The results showed that the use of labor is greater than other production costs, this means that labor is very influential on rice paddy farming, as research conducted by Ref. [14]. shows that labor is the largest component of the production costs of rice farming.…”
Section: Strategizingmentioning
confidence: 96%
“…Peningkatan produktivitas tidak hanya tentang objek pertanian, yaitu benih, lahan, pupuk dan lain sebagainya, melainkan juga subjek (pelaku) usaha pertanian tersebut, yaitu petani. Indonesia harus mencetak petani-petani handal yang mampu meningkatkan hasil produktivitas dan menerapkan sistem pertanian berkelanjutan untuk menuju ketahanan pangan Indonesia (Saragih et al, 2019).…”
Section: Meningkatkan Penggunaan Program Pengendalian Hama Terpaduunclassified
“…Padi merupakan salah satu komoditi tanaman pangan yang mempunyai arti penting bagi masyarakat Indonesia. Hal ini disebabkan karena produk yang dihasilkan dari padi yakni beras menjadi salah satu sumber makanan pokok penduduk Indonesia (Saragih et al, 2019); (Handayani et al, 2020).…”
unclassified